2014
DOI: 10.1111/ggi.12382
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis‐related factors concerning oral and general conditions for homebound older adults in Japan

Abstract: ADL was strongly correlated with life prognosis in homebound older adults. Within the higher ADL participants, occlusal support was related to this outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…We also confirmed the significant associations of functional dependence with comorbid conditions (as indicated by CCI) and smoking history. Our findings agree with those of previous studies showing that lower CCI were significantly associated with increased activities of daily living, as indicated by BI ≥ 60 points . In addition, the present results support the views of previous cohort studies reporting that ever or current smokers were more likely to have greater odds of functional decline …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We also confirmed the significant associations of functional dependence with comorbid conditions (as indicated by CCI) and smoking history. Our findings agree with those of previous studies showing that lower CCI were significantly associated with increased activities of daily living, as indicated by BI ≥ 60 points . In addition, the present results support the views of previous cohort studies reporting that ever or current smokers were more likely to have greater odds of functional decline …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the present findings are generally consistent with those of previous reports showing that the loss of posterior teeth occlusion might cause functional decline among older people. It has been reported that the loss of posterior occlusal support was significantly correlated with decremental changes in the BI . However, these previous reports roughly classified posterior teeth occlusion according to the presence or absence of at least one occlusal support among posterior teeth.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Swallowing function was evaluated using cervical auscultation. For detection of dysphagia, participants were asked to swallow 3 mL of water, and the presence of choking, gargling sounds or other findings as detected by cervical auscultation was considered to indicate the presence of dysphagia . Before carrying out cervical auscultation, a dentist specializing in swallowing function calibrated the evaluators to avoid the occurrence of any inter‐evaluator differences in the evaluation method and criteria.…”
Section: Methodsmentioning
confidence: 99%